The effect of training units by muscle relaxation on alleviating psychological pressure among runners of long-distance distances, class (17-18) years - Khalfa, Imadeddine; Mazroua, said (sports creativity, 2025)
This study aims to find out the effect of the training units on muscle relaxation to alleviate the psychological pressure of the runner, Where the study community included the mandate of M'sila, and the research sample consisted of 10 runners, the youth club of Sidi hamla of athletics in the intentional way, as we relied on the experimental curriculum and the measure of psychological pressure , And the study concluded that there is a positive effect of muscle relaxation on relieving psychological pressure